Magneto-thermal optimization of Prandtl-Eyring nanofluids over an expanding cylinder in a variable porous medium: an entropic and activation energy perspective - Sameh A. Hussein; Anas A. M. Arafa; Khaled Lotfy; Abd Allah A. Mousa; Aly R. Seadawy (Journal of Taibah University for Science)
Heat transfer in non-Newtonian nanofluids is vital for cooling, energy systems, and biomedical applications. This study examines the thermophysical behavior of Prandtl–Eyring nanofluids under magnetohydrodynamic effects within a Riga cylindrical tube, considering variable porosity and thermal radiation. Electromagnetic forcing via the Riga surface regulates flow, while entropy generation analysis evaluates system efficiency. The governing nonlinear equations are simplified using similarity transformations and numerically solved in Mathematica, with validation against existing literature. Results show that stronger magnetic fields reduce velocity by up to 42%, while thermal radiation increases heat transfer by 35%. Entropy generation rises by 60% with enhanced viscous dissipation, signaling higher energy losses. Activation energy reduces concentration gradients, lowering mass transfer by 28%. Porosity variation, surface convection, thermophoresis, and Brownian motion critically influence performance. These findings support the optimized thermal design of nanofluid-based systems in industrial and biomedical settings, where precise thermal regulation is crucial.